The impact of regional integration on Africa's manufacturing exports - Rodgers Mukwaya (Journal of African Trade, 2019)
This paper analyses the impact of Regional Trade Agreements (RTAs) on intraregional manufactured exports in Africa. Using data from 1990 to 2015 for 45 African countries, a structural gravity model was estimated using the Poisson pseudo maximum likelihood estimator that controlled for heteroscedasticity and allowed for bilateral zero trade values between trading partners. The study also accounted for multilateral resistance effects, endogeneity of RTAs, and the phased-in impacts of RTAs. On average, a regional trade agreement led to a 72% increase in manufacturing exports between members within 12 years of the ratification of the trade agreement.
Keywords: F01; F15; 330; Regional trade integration; intra-Africa trade; structural gravity model; manufacturing